PENGARUH KOMITMEN ORGANISASI DAN LINGKUNGAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI - Diah Fitri Nugrahaningtyas, Suprayitno & Edi Wibowo (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2017)
PT Bank Tabungan Negara (Persero) Tbk Branch Solo shows that the behaviorOCB employee was still low, it can be seen from the behavior of employees who are nothelping colleagues who have difficulty in a situation that is being faced by both the taskswithin the organization as well as personal problems of others. The purpose of this studyare: Analyzing the significance of the organization's commitment and workingenvironments on job satisfaction. Analyze the significance of organizationalcommitment, work environment and job satisfaction on organizational citizenshipbehavior. Analyze the significance of the organization's commitment and workenvironment to organizational citizenship behavior is mediated by job satisfaction. Thisstudy uses survey method, the type of data used quantitative and qualitative data, thedata source used primary data and secondary data. The study population was allemployees of PT Bank Tabungan Negara (Persero) Tbk Branch Solo as much as 199employees, the number of samples used by 53 respondents, the sampling technique usingproportional cluster random sampling. Method Data collection: questionnaires anddocumentation. Data analysis technique used to test the validity, reliability test, classicassumption test, and path analysis. In conclusion that: There was a significant effect oforganizational commitment and working environments on job satisfaction. There was asignificant effect of organizational commitment, work environment and job satisfactionon organizational citizenship behavior. There was a significant effect of organizationalcommitment and work environment to organizational citizenship behavior is mediated byjob satisfaction.Keywords: organizational commitment, work environment, job satisfaction,organizational citizenship behavior